The relationship between leadership styles and teachers' job performance of integrated special education programme in Kuching / Soffiah Ahmad - Ahmad, Soffiah (2015)
Leadership is one of the major factors in bringing up the success of an organization. Therefore, the effectiveness of leadership style will ensure a simultaneous effect of progressing the teacher' performance and leading the success of the special education programme. This study investigates senior assistants' leadership styles and teachers' job performance in Integrated Special Education Programme (ISEP) in Kuching. A sample of 64 special education teachers out of 102 populations in the Kuching District was chosen through simple random sampling technique. It was found that the transformational leadership style was most practiced leadership style among Senior Assistants of Special Education. Teachers' job performance was also found to have significant difference between genders, however teachers' job performance showed no significant difference when compared to teachers' length of service. Leadership style revealed no relationship with teachers' job performance in general. However, laissezfaire leadership style showed a significant relationship with teachers' job performance in two of the schools being investigated. Therefore, it is concluded that there was no best leadership styles, nevertheless the best practiced is by matching appropriate leadership style with current situation of the organization. The use of laissez-faire style should be applied when teachers are knowledgeable and in favor of authority in making their own decisions. It was recommended that senior assistants should have multiple leadership style and able to analyze the situation to match with appropriate leadership style in order to enhance better job performance among special education teachers.